Here as the Centre of the World: A Transnational Artistic Research Project (Archis, 2009)
Transnational artistic research project that took place in Taipei, Damascus, Beirut, Khartoum, Diyarbakir, Enschede, producing artwork in local contexts, while simultaneously comparing the productions, to analyze differences and similarities in the thinking and cultural patterns of people. Editors: Lucy Cotter, Gabrielle Schleijpen, Alite Thijsen. Contributors: Lucy Cotter, R. Radhakrishnan, Erwin Jones, Jerlian Tsao, John Heymans, Khalid Khalifa, Pascale Feghali, Tony Chakar, Bechara Malkoun, Susannah Mira, Rania Mamoun, Alite Thijsen, Emily Williams, Kawa Nemir, Ozkan Golpinar, Lilet Breddels, Rana Hamadeh.
English
Keywords: N7560-8266 Visual Arts. Special subjects of art; Sociology